What if Jesus was serious? : a visual guide to the teachings of Jesus we love to ignore - Jethani, Skye, 1976- (Moody Publishers, 2020)
"Let's face it. A lot of Christian resources can feel cheesy, out-of-touch, and a little boring. But when Skye Jethani started doodling and writing up some of his thoughts about God, his Twitter and email list blew up. What If Jesus Was Serious? is a compilation of all-new reflections (and hand-drawn doodles) from Skye. He takes a look at some of Jesus' most demanding teachings in the Sermon on the Mount and pushes us to ask whether we're really hearing what Christ is saying. The visual component of the book makes it memorable and enjoyable to read, and Skye's incisive reflections make it worthwhile for any Christian. If you've traditionally been dissatisfied with Christian devotional resources but love to learn about Jesus and think deeply, this book was written for you"--